Effects of addition of seaweed (kappaphycus alvarezii) on the quality of reduced salt chicken patties - Wolyna Pindi; Lim Wei Qin; Elisha Munsu; Hana Mohd Zaini; Nurul Shaeera Sulaiman; Nor Qhairul Izzreen Mohd Noor (2022)
This study was conducted to determine the effect of salt reduction and the addition of seaweed (Kappaphycus alvarezii) on the quality of chicken patties. In this study, a control sample (1.5% salt and without seaweed) and four chicken patties formulations were studied using two levels of salt (1% and 1.5%) and two levels of seaweed (2% and 4%). The addition of seaweed was shown to improve water holding capacity, emulsion stability and cooking loss (p<0.05) on reduced salt chicken patties (1% salt). Besides, the addition of seaweed decreases the shrinkage of diameter and thickness on chicken patties (p<0.05). However, the addition of seaweed made the patties darker (lower L*-value) (P<0.05). Furthermore, the hardness, chewiness, cohesiveness and elasticity increased with seaweed addition (p<0.05) due to the dietary fibre content in seaweed. Reduced salt chicken patties (1.0%) with seaweed (2% and 4%) showed lower water holding capacity and emulsion stability than chicken patties with seaweed and 1.5% salt content (p<0.05). However, the water holding capacity and emulsion stability of the reduced salt chicken patties (1%) were higher than the control sample (p<0.05). The sensory evaluation showed that the chicken patty with 1.5% salt and 4% seaweed had the highest overall acceptability. However, the overall acceptability of the chicken patties with reduced salt (1%) with 4% seaweed was significantly higher than that of the control sample (p < 0.05). In conclusion, the use of seaweed has the potential to improve the textural properties and emulsion stability of reduced salt chicken patties.